SISTEM PERINGATAN DINI UNTUK KONFLIK SOSIAL DI PERKOTAAN - Moehtadi, Fathoni (Puslitbangkesos, 2006)
Kajian Pendahuluan Pembuatan Peta Digital Kota Tangerang ( Early Warning System for Social Conflict in Cities) Studi to make Digital Map in tangerang City - Social conflict not merely happened at areas which initially are true identified as gristle area. Conflicts with different intensity also exist in the areas where there never happened over hundred years. To lessen possibility the happening of various broader social conflict and stress,early detection of social symptoms in society showing stress signals and conflict require to be gone through. This effort will be easier to conduct if there is a societal early warning system. With the existence of forewarning system, hence areas which tend to have crisis symptom and similar stress can be anticipated with certain actions to avoid. This method will be able to prevent broader conflict and stress acending.